The effects of gender advertising on brand image: the Malaysian context - Mohd. Helmi Abd. Rahim,; Normah Mustaffa,; Lee, Sze Mun (Universiti Kebangsaan Malaysian, 2011)
It is said that gender advertising has caused construction of gender ideals in our society. It forms what are the acceptable and non acceptable temperaments, abilities, skills, activities and behaviors of both genders. Gender advertising has also helped form a tool in advertising, namely gender targeting. This research focuses on the relevance use of gender advertising in advertisements, likeability of the use of gender advertising and perception created through gender advertising in relation to the brand image as viewed by the Malaysian consumer. The research is to identify both the positive and negative effects caused by the various means of gender advertising. The use of gender advertising can either make or break a brand image. The recognition of these effects will in turn contribute to positive usage of gender advertising that does not go beyond the purpose of selling brands to consumer. The method employed is the in-depth interview aided with visual representations to 30 respondents of both genders selectively chosen with criteria either they have involved with the product categories chosen or has had prior brand relationships. In conclusion, the results indicated that gender advertising, if used inappropriately will tarnish brand image and will cause brand to be taken lightly as Malaysian consumer today seek concrete information and representation of the brands.